(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
According to the World Tourism Organization, tourism accounts for about 10% of the turnover of the market of industrial and services in the world. According to the results of the analysis, by 2022, revenues from international tourist attractions are expected to increase. Tourism in the world is increasingly being used as a tourist potential. The rapid growth of this rate in our country was achieved in the autumn.